Implementasi Kebijakan Program Beras Daerah Bagi Rumah Tangga Sasaran Penerima Manfaat (RTS-PM) di Desa Respen Tubu - Fitriani MN; Milwan; Sudirah (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
The Regional Rice Program (Rasda) is an innovation program carried out by the Government of Malinau Regency to empower the community as an effort to improve people's welfare. The aim of the research is to analyze program implementation, supporting factors, and inhibiting factors for this program. The research was carried out using a qualitative approach, data collection techniques through interviews, observation, and studying reports or documents related to research. Researchers analyzed it using the implementation theory put forward by Van Mater and Van Horm. Because of the theory of Van Meter and Van Horn. The results of the research analysis show that the implementation of the Rasda program in general can be carried out well. In terms of standards and policy targets, the Rasda program has been regulated in the form of District Head Regulations, District Head Decrees, and guidebooks. In terms of resources, the implementation of the Rasda program is supported by and through subsidy spending from the APBD (Regional Revenue and Expenditure Budget) of Malinau Regency in the amount of IDR 5,000,000,000.00 (five billion rupiahs) annually. Aspects of communication with the existence of an effective coordination system starting from the village, sub-district, up to the district level. The disposition aspect in the form of delegating monitoring and supervision tasks to the village government supported by the provision of honorariums can increase accountability for the implementation of the Rasda program. Characteristic aspects have been realized through the District Rasda Team which consists of eight OPD (Regional Apparatus Organizations) and Perumda (Regional Public Company) Intimung. Aspects of the social, economic and political environment show that the Rasda program is able to help meet food needs. The factor that supports the implementation of the Rasda program is the district head's high commitment to production and distribution. The inhibiting factors are limited regional rice productivity and limited facilities, infrastructure, and facilities.